ANALISIS PEMILIHAN SUPPLIER PART MESIN PRIMARY PACKAGING PADA PT XYZ - Rahmadhani, Ara; Arista, Anggia (Computer Science and Industrial Engineering, 2023)
PT XYZ is a company engaged in the field of medical devices, namely contact lenses. PT XYZ carries out its production activities using Primary Packaging machines in the form of O-ring Viton parts. Based on observations, the supplier selection process for O-ring Viton parts is less efficient. To overcome this issue, the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods can be used. This study aims to provide supplier rankings for consideration in obtaining the best suppliers so that they can work together in the long term. The results showed that there were 4 criteria and 12 sub-criteria, where the Quality criterion (K2) had the greatest value (0.6237), the Accuracy in the Number of Delivery sub-criteria (D1) had the greatest value (0.7215), and based on the calculation of the AHP method which became the priority the first is the IHI supplier (0.4144). Based on the calculation of the TOPSIS method, the first priority is IHI suppliers with a preference value (0.7922). The results of this study show that IHI suppliers are a top priority and are able to meet all the raw material needs for Viton O-ring parts at PT XYZ.